The doubletime and CKII kinases collaborate to potentiate Drosophila PER transcriptional repressor activity. - Nawathean, P.; Rosbash, M. (Molecular Cell, 2004)
In all genetically studied model organisms, a negative feedback loop of gene expression contributes to the circadian rhythm mechanism. In the Drosophila system, it has been proposed that the delay between the synthesis and function of clock proteins is due to phosphorylation-regulated nuclear entry. To test this hypothesis, we assayed the relationship between PER phosphorylation, nuclear localization, and transcriptional repression activity in cultured S2 cells. The results indicate that the two putative PER kinases DBT and CKII work together to phosphorylate PER and increase repression activity. Experiments combining kinase inhibition with inhibition of PER nuclear export suggest that phosphorylation directly affects PER repression activity and that PER nuclear localization is an indirect consequence of the association of active PER with DNA or chromatin. This interpretation suggests further that the circadian regulation of PER nuclear localization in flies reflects changes in PER transcriptional activity rather than in PER nuclear import or export activity.